Intramuscular Haemangioma with Diagnostic Challenge: A Cause for Strange Pain in the Masseter Muscle - Krithika Chandrasekar Lakshmi; Sathasivasubramanian Sankarapandiyan; Venkata Sai Pulivadula Mohanarangam (Hindawi Limited, 2014)
Intramuscular hemangiomas are unique vascular tumors which are benign in nature, most commonly occurring in the trunk and extremities. When present in head and neck, they most frequently involve the masseter and trapezius muscles, accounting for less than 1% of all hemangiomas. Most of these lesions present with pain and discomfort and some patients may demonstrate progressive enlargement. Due to their infrequency, deep location, and unfamiliar presentation, these lesions are seldom correctly diagnosed clinically. Our report is a clinically misdiagnosed case of a painful soft tissue mass in the right side masseteric region of a 23-year-old female patient, confirmed as intramuscular hemangioma based on imaging studies and histopathologic examination, treated by surgical excision which had no recurrence after a 3-year followup.